Decoupling structure for high-bandwidth multiport monopole antennas in K-band and 5G applications - Abbasi, Muhammad Inam; Sehrai, Daniyal Ali; Kiani, Saad Hassan; Ali, Tanweer; Kamarudin, Muhammad Ramlee; Algarni, Abeer D.; Elmannai, Hela (Wiley, 2024)
Tis paper introduces a multiport monopole antenna featuring high isolation and a broad operating bandwidth, specifcally designed for K-band and 5 G applications. Te proposed antenna confguration comprises four antenna elements assembled toachieve a compact design. A 0.254 mm thick Rogers RT-5880 substrate is used, with an overall size of 24 × 22 mm. Each antenna element is supported by a truncated ground plane, and four symmetrical slots are introduced into the radiating structures. Asa result, the proposed multiport antenna covers a frequency band of approximately 18–27 GHz, based on the −10 dB criterion, providing a wide bandwidth of nearly 9 GHz. Te separation between the antenna elements is about 4.5 mm. Additionally, a decoupling structure is inserted between the radiating elements to enhance isolation within the desired band, also resulting in a minor improvement in the operating bandwidth. Several performance metrics, including total active refection coefcient(TARC), diversity gain (DG), envelope correlation coefcient (ECC), and channel capacity loss (CCL), are evaluated and show satisfactory performance within the operating bandwidth. Te proposed antenna achieves more than 75% radiation efciency. Teoverall performance of the multiport antenna indicates its potential for K-band and 5 G applications.